Village Authority in Tourism Management to Support Income Increase Desa Kemuning, Kecamatan Ngargoyoso, Kabupaten Karanganyar - Rossi Filia Maladi; Adriana Grahani Firdausy; Maria Madalina (Cakrawala Repositori IMWI, 2024)
Village development is an important aspect in the development of the Indonesian Nation. One sector that can be utilized for village development is tourism. Village has the authority to develop its tourism as a form of managing the potential of the village. Village tourism in the process of its development is inseparable from obstacles such as low human resources, conflicts between villagers in the development of village tourism, etc. This research discusses how the authority of Kemuning Village in tourism management to support the enhancement of Kemuning Village's original income and what obstacles the Kemuning village government experiences in managing the village's tourism potential to support village income. This research is a type of empirical legal research with a descriptive research style and a qualitative approach. The data collection techniques used are field research and literature study. Based on this research, Kemuning Village has already executed some of its authorities in tourism management to support the increase of village income, but there are also some authorities that have not been executed by the Kemuning Village government. The obstacles experienced by the Kemuning Village government in managing tourism potential to support village income are the lack of people who understand and can utilize the potential of the tourism sector, the lack of coordination between the Kemuning Village Government and the Karanganyar Regency Government, the implementation of BUM Desa that is not yet optimal, and the absence of village regulations related to tourism management and levies on tourist business services.